Impact of probiotic administration on the health and fecal microbiota of young calves: A meta-analysis of randomized controlled trials of lactic acid bacteria - Signorini Porchietto, Marcelo Lisandro (2012)
Before weaning, dairy calves are susceptible to many pathogens which can affect their subsequent performance. The use of lactic acid bacteria (LAB) has been identified as a tool to maintain the intestinal microbial balance and to prevent the establishment of opportunistic pathogenic bacterial populations. However, a consensus has not been reached as to whether probiotics may be effective in reducing the prevalence of gastrointestinal diseases in young calves. The aim of this meta-analysis was to assess the effect of probiotics on diarrhea incidence and the intestinal microbial balance. LAB supplementation has been shown to exert a protective effect and to reduce the incidence of diarrhea (relative risk, RR =0.437, 95% confidence interval (CI) 0.251 ?0.761). In the subanalysis,this protective effect of the probiotics against diarrhea was observed only in trials that used whole milk (RR=0.154, 95%CI 0.079 ?0.301) and trials that used multistrain inocula (RR=0.415, 95%CI 0.227 ?0.759). Probiotics did not improve the fecal characteristics (standardized mean difference, SMD =0.4904, 95%CI 1.011 ?0.035) and were unable to change the LAB:coliforms ratio (SMD =0.016, 95%CI 0.701 ?0.733). Probiotics showed a beneficial impact on the LAB:coliforms ratio in the subanalysis that included trials that used whole milk (SMD =0.780, 95%CI 0.141 ?1.418)and monostrain inocula (SMD =0.990,95%CI 0.340 ?1.641).The probability of significant effects (probiotic positive effect) in a new study was >0.70 for diarrhea and fecal consistency. Whole milk feeding improved the action of the probiotic effect on the incidence of diarrhea and LAB:coliforms ratio.The probability to find significant effects in the diarrhea frequency and LAB:coliforms ratio was higher (P >0.85) if the new studies were conducted using whole milk to feed calves. This paper defines the guidelines to standardize the experimental designs of future trials. LAB can be used as growth promoters in calves instead of antibiotics to counteract the negative effects of their widespread use.